2017
DOI: 10.1016/j.carbon.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between X-ray diffraction and Raman spectra of 16 commercial graphene–based materials and their resulting classification

Abstract: Structural properties of sixteen (16) commercial samples of graphene-based materials (GBM) labelled as graphene, graphene oxide or reduced graphene oxide are investigated at room temperature using X-ray diffraction (XRD) and Raman spectroscopy. Based on the observed correlation between the results obtained with these two techniques, these samples are classified into three groups: Group A of seven samples consisting of graphitic nanosheets with evaluated thickness ≃20 nm and exhibiting both the 2H and 3R phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 22 publications
6
39
0
Order By: Relevance
“…In Figure 10, it can be seen clearly that the prominent peaks of graphene for (002), the crystal plane was positioned at 2θ = 26.4° and (101) the crystal plane was positioned at 2θ = 43.0°, which is consistent with other studies reported previously [47][48][49]. Thus, it was confirmed by XRD spectrum that multilayered graphene structure was obtained.…”
Section: Xrd Characterizationsupporting
confidence: 88%
“…In Figure 10, it can be seen clearly that the prominent peaks of graphene for (002), the crystal plane was positioned at 2θ = 26.4° and (101) the crystal plane was positioned at 2θ = 43.0°, which is consistent with other studies reported previously [47][48][49]. Thus, it was confirmed by XRD spectrum that multilayered graphene structure was obtained.…”
Section: Xrd Characterizationsupporting
confidence: 88%
“…Notably, the X-ray diffraction pattern of FLGs is dominated by the characteristic graphitic peak. [68] This is because around 30 %o ft he flakes are multilayer ( % 5nm) as ar esult of the WJM process, but this is enough to dominate the diffraction spectrum. [45] More importantly,t he diffraction pattern of the S-FLGs active material is composed of peaks corresponding to the two pristine materials, suggesting that the production process does not deteriorate the crystal quality of the materials involved.…”
Section: Resultsmentioning
confidence: 99%
“…The data were collected between scattering angles of 5-90°and at a scan rate of 2°·min −1 . [26], whereas the G band belongs to the doubly degenerate E 2 g mode at the Brillouin zone center [27]. The integrated intensity ratio of the D and G bands (I D /I G ratio) was about 0.22.…”
Section: Chemical and Structuralmentioning
confidence: 97%